Masificación del Wushu con sus fundamentos técnicos y metodológicos en niños y jóvenes de la Federación Deportiva de El Oro en la ciudad de Machala durante el año 2012-2013. - Torres Asanza, Roberto Carlos (2013)
The research paper briefly outlines the technical and methodological foundations of wushu in the teaching-learning process, since most teachers do not use the technical and methodological foundations to teach this sport in the Gold Sports Federation, causing in the Practicing demotivation and a lack of desire to learn the techniques.